2021
DOI: 10.1093/toxsci/kfab052
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Reconstruction of the Early Hepatic Transcriptomic Landscape After an Acetaminophen Overdose Using Single-Cell RNA-Sequencing

Abstract: An acetaminophen (APAP) overdose is the most common cause of acute liver failure in the United States. A hallmark characteristic of APAP hepatotoxicity is centrilobular necrosis. General, innate mechanisms such as lower amounts of GSH and higher Cyp2e1 expression in pericentral (PC) hepatocytes are known to contribute to the differences in susceptibility to cell injury between periportal (PP) hepatocytes and PC hepatocytes. While a sequence of molecular events involving formation of the reactive metabolite N-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 52 publications
4
22
0
Order By: Relevance
“…g ., NAPQI) leading to the release of NRF2 by KEAP1 187 , whereby NRF2 can translocate to the nucleus and activate antioxidant defense protocols 188 . Importantly, induction of critical genes involved in hepatic GSH resynthesis ( Gclc and Gclm ) following APAP toxicity 36 , 189 can mitigate injury as GSH can directly sequester NAPQI and detoxify reactive oxygen and peroxynitrite. Other canonical genes regulated by NRF2 include NAD(P)H:quinone oxidoreductase 1 (NQO1), glutathione peroxidase, and the conjugation enzymes, UDP-glucuronosyltransferases (UGT) and glutathione- S -transferases (GST) 190 .…”
Section: General Recommendations For Investigating Therapeutic Efficacy and Mechanisms Of Actionmentioning
confidence: 99%
“…g ., NAPQI) leading to the release of NRF2 by KEAP1 187 , whereby NRF2 can translocate to the nucleus and activate antioxidant defense protocols 188 . Importantly, induction of critical genes involved in hepatic GSH resynthesis ( Gclc and Gclm ) following APAP toxicity 36 , 189 can mitigate injury as GSH can directly sequester NAPQI and detoxify reactive oxygen and peroxynitrite. Other canonical genes regulated by NRF2 include NAD(P)H:quinone oxidoreductase 1 (NQO1), glutathione peroxidase, and the conjugation enzymes, UDP-glucuronosyltransferases (UGT) and glutathione- S -transferases (GST) 190 .…”
Section: General Recommendations For Investigating Therapeutic Efficacy and Mechanisms Of Actionmentioning
confidence: 99%
“…APAP-induced liver injury is initiated by its metabolism by cytochrome P450, predominantly CYP2E1, to a reactive metabolite. This mainly occurs in the hepatocytes surrounding the central vein in the liver, where CYP2E1 is highly expressed . This zonated pattern of CYP2E1 expression correlates with the characteristic necrosis of hepatocytes surrounding the central vein seen after an APAP overdose.…”
Section: Discussionmentioning
confidence: 79%
“…This mainly occurs in the hepatocytes surrounding the central vein in the liver, where CYP2E1 is highly expressed. 12 This zonated pattern of CYP2E1 expression correlates with the characteristic necrosis of hepatocytes surrounding the central vein seen after an APAP overdose. This dependence of hepatotoxicity on regional metabolism within the liver lobule illustrates the importance of understanding local variations in APAP metabolism within the liver since regional concentrations of APAP-derived metabolites may be differentially toxic to hepatocytes around the central vein or the portal triad.…”
Section: ■ Discussionmentioning
confidence: 83%
“…As for the digestive system, Umbaugh et al reconstructed the early transcriptomic acetaminophen liver lobule using single-cell RNA sequencing and elucidated the molecular sequences of periportal and pericentral hepatocytes in different response to acetaminophen exposure. The authors found that periportal hepatocytes developed along the acetaminophen stress axis to oxidative stress, while pericentral hepatocytes continued to develop along the stress axis activated by mitogen-activated protein kinase genes . Zhang et al used single-cell RNA-seq to investigate the mechanism of hepatotoxicity of AFB 1 to S phase-arrested L 02 cells.…”
Section: Applications Of Single-cell Toxicogenomicsmentioning
confidence: 99%